Analysis of the Port Environment for the Export of Green Hydrogen (Global Journal of Science Frontier Research, 2023)
The Paris Agreement, signed in 2015 during the 21st Conference of the Parties (COP21) of the United Nations Framework Convention, was an important milestone for the establishment of ambitious and concrete climate goals, especially with regard to the reduction of greenhouse gas emissions effect and energy security. To this end, several countries committed to achieving the goals established by the Paris Agreement are in the energy transition phase from a carbon-based matrix to a cleaner, low-carbon matrix. In this context, green hydrogen emerges as a clean energy alternative, being a favorable option to move towards the current process of decarbonization of global economies (in particular, industries and the mobility sector) and to achieve the goals established in the Agreement. Brazil, in turn, prepared an energy expansion plan to compose its matrix with a 45% share of clean energy by the year 2030, however, with regard to the use of green hydrogen as a direct source of energy or energy vector, the country is still in the incipient stage of research and development (R&D).
Keywords: green hydrogen; supply chain; port environment